Change and the Poetics of Plenitude in Wallace Stevens and John Ashbery - Bartczak, Kacper (Text Matters: A Journal of Literature, Theory and Culture, 2015)
The essay attends to a paradox found in some crucial poetic efforts by Wallace Stevens and John Ashbery. In some of their most important poetic works Stevens and Ashbery take on the task of positioning the poem toward the plurality of reality, the plurality that is concentrated in the phenomenon of change. As they do so, they invariably encounter a tension within the poem itself: as the poem merges with the flow of changes in the external world-the physical changes in time and space-it also calls up permanent forms of imaginative purposive capability of attending to change, envisioning it, or, indeed, of installing it. These forms must be more permanent than it is postulated by some theories of the poetics of transitiveness, which are polemically discussed in the text. The tension between the element of change and permanence is what allows the poems of Stevens and Ashbery-each poet finding his own aesthetic and epistemic strategy-to put the poem forward not as an external “representation” of change, but as the very source of the abundant possibilities of producing world descriptions in which the notion of change may be meaningful. Such positioning of the poem is what I am calling “the poetics of plenitude.” This poetic strategy makes the poem an aesthetic counterpart to the epistemic action of developing an inquiry, and I am building a definition of this term by reference to the classical pragmatist theory of inquiry. This move is related to my treating Stevens and Ashbery as the poets belonging to the Emersonian-pragmatist intellectual and aesthetic tradition. The paradoxes of change and permanence discussed in the text are treated as inherent in this tradition.